Pentingnya pendidikan agama Islam di sekolah: Analisis kualitatif terhadap dampaknya pada pembentukan - Nuriyah, Afrizatun (Maliki Interdisciplinary Journal, 2024)
Islamic religious education in schools has an important role in shaping the character of students, not only in cognitive but also moral and ethical aspects. This article aims to analyze the importance of Islamic religious education and its impact on the formation of student character through a qualitative approach. The research method uses a qualitative approach with case studies, involving interviews with teachers, students, and parents, as well as direct observation in several schools in Indonesia. The results showed that Islamic religious education plays a significant role in improving the morale, Ethics, Religious Identity, and positive character of students. In addition, religious education also has a positive impact on student academic achievement. Therefore, the integration of religious education in the school curriculum needs to be supported and developed to produce a generation that is intellectually intelligent and has a strong character. Suggestions include the development of a broader and relevant curriculum, ongoing training for religious teachers, and the active involvement of parents in the religious education of their children. Thus, Islamic religious education is not only a lesson in the classroom, but also an integral part of students ' daily lives to help shape a better future.